The mosaic inscription from Caminreal (Hispania Citerior; MLH E.7.1 = K.5.3): Thirty years of research (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Status of the issue of mosaic Iberian Inscription from the ar-chaeological site of La Caridad (Caminreal). This paper analyzes the exten-sive bibliography of this inscription, organized in four principal sections: the name likine; the term ekiar; the place name; and the likine’s indentity.
Keywords: Iberian language; Mosaic inscription; Signature craftsman; Opus signinum; Musiuarius